Investigation on corrosion properties of carbon-carbon composites - Gribanov, Yu.A.; Gurin, I.V.; GujdaGujda, V.V.; Bukolov, A.N.; Kolosenko, V.V. (Вопросы атомной науки и техники, 2020)
The corrosion resistance of carbon-carbon composite materials (C–C composites) was studied in a corrosive media of coolant NaF+ZrF₄ salt (a model heat-transfer) at 700 °С in the air flow. It has been shown that C–C composite material is resistant to the model heat-transfer even under conditions of critical temperature accident. The main mechanism that leads to the C–C composite corrosion is a mechanism of composite material oxidation due to the contact with the air. The study has evidenced that the C–C composite burn-up rate well correlates with the pyrocarbon matrix content in the composite, the matrix content increase by 25...30% results in the composite corrosion resistance increase by a factor of 2–4. So, by developing corrosion-resistant carbon-carbon composites one has a problem of finding an optimum fiber-matrix ratio in the composite. It has been confirmed experimentally that by silication of C–C composites with the use of the methods which were developed in NSC KIPT it is possible to increase the service life of products under simulated accident conditions by a factor of 7 – 7.5.